Putting Into Circulation or Driving an Unlicensed Motor Vehicle Pursuant to the New Romanian Penal Code - ZAZULA, Bela (Journal of Legal Studies, 2015)
The lawgiver of the new Penal Code proposed to charge into offences some deeds that endanger the public safety as social value protected by the penal norms and which, in their turn, include a series of values that might be harmed due to a breach of some rules established for the performance of certain activities, inhere for the social life, as well as those that set out, among others, the traffic safety on public roads.